Magnetic field control over the axial character of Higgs modes in charge-density wave compounds - Dirk Wulferding; Jongho Park; Takami Tohyama; Seung Ryong Park; Changyoung Kim (Nature Communications)
Abstract Understanding how symmetry-breaking processes generate order out of disorder is among the most fundamental problems of nature. The scalar Higgs mode – a massive (quasi-) particle – is a key ingredient in these processes and emerges with the spontaneous breaking of a continuous symmetry. Its related exotic and elusive axial counterpart, a Boson with vector character, can be stabilized through the simultaneous breaking of multiple continuous symmetries. Here, we employ a magnetic field to tune the recently discovered axial Higgs-type charge-density wave amplitude modes in rare-earth tritellurides. We demonstrate a proportionality between the axial Higgs component and the applied field, and a 90° phase shift upon changing the direction of the magnetic field. This indicates that the axial character is directly related to magnetic degrees of freedom. Our approach opens up an in-situ control over the axial character of emergent Higgs modes.